LAND USE CHANGES IN THE TRANS-BOUNDARY AMUR RIVER BASIN IN THE 20TH CENTURY - Victor Ermoshin; Sergey Ganzey; Takauyki Shiraiva (Geography, Environment, Sustainability, 2013)
All distinctions in the economic and nature protection policy of the neighboring states are well reflected and shown within trans-boundary river basins. The parts of trans-boundary geosystem of one country can experience an essential negative influence from rash decisions in the field of nature use and nature protection policy of the neighboring state. The Amur River Basin covers the territories of Russia, the Peoples Republic of China, Mongolia and Democratic People’s Republic of Korea and occupies more than 2 million km2. The most intensive development of the basin territory has started since the middle of the 19th century. We compiled two maps of land use in the Amur River basin in the 1930–1940s and in the early 21st century. Results showed that, negative dynamics is marked for forest lands, meadows, wetlands and mountain tundra. The basic features in the change of land use within national parts of the basin in Russia, China and Mongolia are analyzed. The comparative analysis of land use peculiarities of the countries for the last 70 years has been done.